(untitled) (Nóema, 2013)
The theory of biological Evolution after the recent discoveries of molecular biology, immunology and embryology: the “adaptive mutation” discovery in bacteria and its reality in higher organisms. Statistics of rare events and “intelligent design”. Heredity of the characters acquired during epigenesis: Darwin and Lamarck. Structure of the brain and human mind: the role of genetic inheritance and the one of the ambient and of the experiences in the formation and evolution of the mind and personality. Arbitrarity and redundancy in the evolution of living organisms and that of human languages.